5x-(-12)+20=-3

Simple and best practice solution for 5x-(-12)+20=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(-12)+20=-3 equation:


Simplifying
5x + -1(-12) + 20 = -3

Multiply -1 * -12
5x + 12 + 20 = -3

Reorder the terms:
12 + 20 + 5x = -3

Combine like terms: 12 + 20 = 32
32 + 5x = -3

Solving
32 + 5x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-32' to each side of the equation.
32 + -32 + 5x = -3 + -32

Combine like terms: 32 + -32 = 0
0 + 5x = -3 + -32
5x = -3 + -32

Combine like terms: -3 + -32 = -35
5x = -35

Divide each side by '5'.
x = -7

Simplifying
x = -7

See similar equations:

| (5/9)p=-20 | | 99-2x=9x+15 | | 0.50x+0.45(50)=45.5 | | 10x+15=105 | | 5z+10-3z=9+z+7 | | x/10=-3+26 | | 2m^2+3m-27=0 | | 2x+7=x+12 | | 36y^2+81y+45= | | 4(2x-3)=8(x-1) | | x^4-2x^2+3=0 | | h=24+8t+-16t^2 | | (3b+5)(b+5)=0 | | -8x-22=-182 | | 2x-3x-3=-1 | | x+5/3=7x-2/5 | | 8-15=z/-5 | | 37=-5(6n-6) | | P^2=-8-9p | | 5z-4=-8+z | | 6(t-5)+8t=7(2t+2)-10 | | 8x+9=-31 | | 9m-7=17+5m | | 8+2+x=6+4 | | -2x-18x-33=-7 | | 9p^2-18p+8= | | 3x+25+6x+20=180 | | 3(n+4)=1+4n | | -4.6=92.0 | | 5z=9 | | 5x+4=7x-9 | | 5r^2-40r=0 |

Equations solver categories